Primary omental infarction: a report of a series of cases in an Indian tertiary care hospital - Ray, Ruru; Sunny, Ann; Ashwath, Giridhar; Rozario, Anthony Prakash; Sima, Rahul (International Surgery Journal, 2020)
Primary omental infarction is a relatively rare and often presents as right sided abdominal pain. It is often diagnosed as appendicitis and is usually picked up intra-operatively, or - as often seen nowadays - on imaging. We describe a series of four cases of primary omental infarction that presented to us with varying clinical features. Three of them had a short history of right sided abdominal pain, whereas the fourth patient had a longer history of left sided abdominal pain. All 4 were managed operatively, with the fourth having presented with an intra-abdominal abscess that required laparotomy. Primary omental infarction is a diagnosis which must be considered in any case of acute abdomen. Cases diagnosed with certainty on imaging may be managed conservatively but must be followed up closely. Need for surgical intervention should be considered in select cases.